2002
DOI: 10.1264/jsme2.2002.82
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transfer of Nodulation Genes in Soils and Microcosms from Bradyrhizobium japonicum to B. elkanii.

Abstract: We investigated the horizontal transfer of nodulation (nod) genes to a Bradyrhizobium elkanii strain, lacking common nod genes as a recipient, in soils and microcosms using selection systems of antibiotic resistance and legume nodulation. We observed the horizontal transfer of nod genes at 4°C in Nakazawa soil where peculiar strains (HRS strains) of B. japonicum harboring high copy numbers of insertion sequences dominated. In microcosms containing HRS strains as donors, we detected a similar horizontal transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
2
26
0
2
Order By: Relevance
“…This mechanism is also responsible for speciation and sub-speciation in bacteria (6). In the case of rhizobia, Minamisawa et al (22) suggested the potential horizontal transfer of nod genes among bradyrhizobia and other bacterial populations in soil environments. Similarly, Bailly et al (2) suggested that during the evolution of Medicago symbionts, horizontal transfer of nod genes might have occurred either to the common ancestor of the two Ensifer species or to one Ensifer species followed by the other.…”
mentioning
confidence: 99%
“…This mechanism is also responsible for speciation and sub-speciation in bacteria (6). In the case of rhizobia, Minamisawa et al (22) suggested the potential horizontal transfer of nod genes among bradyrhizobia and other bacterial populations in soil environments. Similarly, Bailly et al (2) suggested that during the evolution of Medicago symbionts, horizontal transfer of nod genes might have occurred either to the common ancestor of the two Ensifer species or to one Ensifer species followed by the other.…”
mentioning
confidence: 99%
“…The surface-sterilized soybean seeds (Glycine max cv. Enrei) were germinated and transplanted to a Leonard jar (25,48), which contained sterile vermiculite and nitrogen-free sterilized nutrient solution (31,39). The cell suspension of B. japonicum (1 ml) was used for inoculation at 1 ϫ 10 7 cells per seed.…”
mentioning
confidence: 99%
“…For the nitrogen fixation experiment, soybeans were grown in pots (1 liter) filled with vermiculite in a phytotron (Koitotron type KC; Koito Industries, Tokyo, Japan). A nitrogen-free sterilized nutrient solution was periodically supplied to the pots (31,39). N 2 O uptake, 15 N-N 2 emission, and 15 N incorporation by nodules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds were then immersed in 0.5% (vol/vol) sodium hypochlorite for 1 min and washed 10 times with sterile distilled water. Finally, the seeds were placed in sterilized plates containing tissue paper wetted with sterile distilled water for 2 days at 30°C in the dark and then transplanted to a Leonard jar (CUL-JAR300; Asahi Glass Co., Ltd., Tokyo, Japan) containing sterile vermiculite and nitrogen-free nutrient solution (28). After transplantation, the seedlings were inoculated with bacteria at 1 ϫ 10 8 cells per plant.…”
Section: Methodsmentioning
confidence: 99%